Insomnia Symptoms in the General Population During the COVID-19 Pandemic - Halsøy, Øyvind; Johnson, Sverre Urnes; Hoffart, Asle; Ebrahimi, Omid V. (Frontiers in Psychiatry, 2021)
This empirical study aims to investigate factors associated with insomnia symptoms during the COVID-19 pandemic in 4921 Norwegian adults. Participants were queried across two time-points. Relevant risk factors and psychological correlates at the first time-point and insomnia symptoms were measured three months later, allowing for the investigation of concurrent associations as well as associations across time. Insomnia symptoms were measured with the Bergen Insomnia Scale. The results revealed that individuals reported higher mean levels of insomnia symptoms at T2, compared to pre-pandemic surveys (p < .0001, Cohen's d = 0.29.). Individuals who predominantly socially distanced reported higher mean levels of insomnia symptoms than those who did not predominantly distance. Females, individuals with lower education levels, individuals who had lost their job, and individuals with a pre-existing psychiatric disorder reported the most symptoms. The regression model showed that physical exercise, was associated with less symptoms of insomnia. Symptoms of health Anxiety, symptoms of depression, unhelpful coping strategies, worry about job and economy, and older age were all associated with higher levels of insomnia symptoms. These findings highlight particularly vulnerable subgroups, as well as providing clinicians with key areas of intervention to help individuals suffering from insomnia symptoms.